Fresh crushed garlic exhibits superior allicin and pyruvic acid stability, while fresh sliced garlic leads in phenolic and antioxidant content - Rababah, Taha; Al-U'datt, Muhammad; Angor, Malak; Alsaad, Ahmad; Akkam, Yazan; Gammoh, Sana; Magableh, Ghazi; Smadi, Tamara; Almajwal, Ali; Yucel, Sevil; Hamadneh, Bandar N.; Bartkute-Norkuniene, Vaida; et al. (ELSEVIER, 2025)
This study investigates the stability of allicin, phenols, and antioxidants in different forms of garlic (fresh whole peeled, fresh sliced, fresh crushed, and dried slices) under various storage conditions (0 to 2 days at 4 degrees C and 20 degrees C). The garlic contents of allicin and pyruvic acid, total phenols, and antioxidant activity were determined. Sensory evaluation of hummus samples, enriched with garlic in varying treatments, was conducted by 40 participants to assess acceptability and intensity of flavor, aroma, and pungency. Fresh garlic exhibited allicin levels ranging from 0.6 to 32.14 mg/g, while dried garlic showed significantly lower levels (3.77 to 6.68 mg/g). Maximum allicin stability in fresh garlic was observed after 10 min at 20 degrees C, with pyruvic acid peaking after 10 min at 4 degrees C. Freshly sliced and crushed garlic retained the highest phenol content and antioxidant activity immediately after preparation, whereas dried garlic had reduced levels due to thermal processing. Consumer testing revealed that hummus with fresh crushed garlic at 10 min and 20 degrees C was preferred, while dried garlic at 20 min and 4 degrees C had the strongest flavor and aroma. In conclusion, fresh crushed garlic is optimal for allicin and pyruvic acid content, while fresh sliced garlic excels in phenol and antioxidant levels; drying notably diminishes these beneficial compounds, affecting flavor and consumer preference. According to these results, consuming the fresh garlic after 10 min of mashing it at room temperature is recommended for optimal allicin yield and pungency.
Keywords: Allicin; Antioxidants; Nutrition; Drying; Storage; ALLIUM-SATIVUM L.; QUANTITATIVE-DETERMINATION; BIOACTIVE COMPONENTS; QUANTIFICATION; CONSTITUENTS; PERCEPTION; KINETICS; BENEFITS; SUGAR; Food Science & Technology